The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3389/fcell.2022.1020958
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic variation: A major player in facilitating plant fitness under changing environmental conditions

Abstract: Recent research in plant epigenetics has increased our understanding of how epigenetic variability can contribute to adaptive phenotypic plasticity in natural populations. Studies show that environmental changes induce epigenetic switches either independently or in complementation with the genetic variation. Although most of the induced epigenetic variability gets reset between generations and is short-lived, some variation becomes transgenerational and results in heritable phenotypic traits. The short-term ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 313 publications
(368 reference statements)
0
6
0
1
Order By: Relevance
“…S20B). While purely epigenetic variation is well-known [74,75], our analysis did not distinguish between this and the case when the epigenetic variation that defines expression variation is itself defined by an underlying genetic or structural variation. We showed that two structural features of lincRNA loci – their TE content and their copy number – are associated with silencing and increased expression and epigenetic variation (Fig.…”
Section: Discussionmentioning
confidence: 82%
“…S20B). While purely epigenetic variation is well-known [74,75], our analysis did not distinguish between this and the case when the epigenetic variation that defines expression variation is itself defined by an underlying genetic or structural variation. We showed that two structural features of lincRNA loci – their TE content and their copy number – are associated with silencing and increased expression and epigenetic variation (Fig.…”
Section: Discussionmentioning
confidence: 82%
“…S20B ). While purely epigenetic variation is well known ( Xu et al 2019 ; Rajpal et al 2022 ), our analysis did not distinguish between this and when the epigenetic variation that defines expression variation is itself defined by an underlying genetic or structural variation. We showed that 2 structural features of lincRNA loci—their TE content and their copy number—are associated with silencing and increased expression and epigenetic variation ( Figs.…”
Section: Discussionmentioning
confidence: 86%
“…Plants exhibit phenotypic plasticity in response to habitat heterogeneity by altering their morphological characteristics and cellular metabolism to form stable heritable structural features [ 27 ]. Under the influence of endogenous phytohormones and environmental signals, plants display general heterogeneity in branching development patterns, growth rates, and other traits throughout their life cycle [ 28 ]. This phenotypic plasticity enables plants to evolve in response to harsh environments by altering their morphology and physiology to enhance their survival and reproduction [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%